Pengetahuan, sikap Remaja Putri dan Dukungan Petugas Kesehatan terhadap Konsumsi Tablet Besi Folat SMKN 1 Bangsri Jepara: Sebuah Studi Cross Sectional - Sari Tirthawati; Ali Rosidi; Enik Sulistyowati; Rr. Annisa Ayuningtyas (Universitas Muhammadiyah Semarang, 2020)
The iron-folate tablets program on adolescent girls for anemia prevention still facing some obstacles, especially adherence to consuming them. This study aimed to determine the relationship between knowledge, attitudes, and health worker’s support with the adherence of iron-folate tablets consumption. This study was a cross-sectional study, conducted at SMKN 1 Bangsri Jepara. Anumber of 73 respondents were selected by stratified random sampling. The data were obtained through interviews using a questionnaire, and analyzed using Rank Spearman test.The results showed that most respondents had moderate knowledge (54.8%), good attitude (69.9%), and good health worker’s support (65.8%). As much as 82.2% of adolescent girls did not comply to consume iron-folate tablet which were given once in a week. The unpleasant smell and taste of iron-folate was the reason for the respondent’s (31,5%) disiobedient. The statistical tests showed that there were relationships between knowledge and respondent’s compliance (p=0.004;r=0.334), attitude and respondent’s compliance (p=0.000;r=0.543) and health worker’s support with the respondent’s compliance (p=0.000;r=0.544).The health worker’s support variable is the most dominant variable related to the compliance of iron-folate tablets consumption. It is shown that the higher the support from health workers, the higher the compliance of iron-folate tablets consumption.Keywords: Compliance, adolescent girl, iron-folate tablet consumption